La responsabilidad del franquiciante por actos del franquiciado frente a terceros (2016)
The new strategies of the market have been appropriating societies under the named globalization, which come as a strategy to expand its vision of economic development, talking about the figure of the franchise, it is structured under a contract which stipulates commitments, rights, terms of conditions and responsibilities between the two parties. The last one is the object of study of this research, it is focused to go forward the responsibility of the franchiser, when this one sees for the non problems caused to the patrimony and damages caused to a third part, it could be consumers or clients of the franchise. To arrive to a conceptual descriptive analysis, the most relevant precedents are mentioned, as well as national and international jurisprudence, where noted, the perspective of each of the courts and tribunals, if the franchisor is called to respond or not.These criteria help us to conclude that will be the consumer’s rights of protection which will determine the responsibility of the franchisor.